Corporate Social Responsibility as an International Strategy - Keinert, Christina (Physica-Verlag, 2008)
CSR, a concept aimed at determining the amount of responsibilities to be shouldered by private business toward stakeholder groups and society at large, deserves to be dealt with in considerable detail and not simply as another "PR fuzz" or marketing gag. As a model, CSR epitomises the old saying "business is business"; offering broader stakeholder management which can be seen as a competitive advantage.